FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA ANAK USIA 0-59 BULAN DI WILAYAH KERJA PUSKESMAS SIMARMATA KECAMATAN SIMANINDO KABUPATEN SAMOSIR TAHUN 2013 - Ira Primona Simarmata; drh. Rasmaliah M.Kes; drh. Hiswani M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Diarrhea is a condition where there is abnormal defecation frequency (more than 3 times / day) as well as changes in the content (more than 200 garm / day) and liquid stool consistency. According to Indonesia Health Profile (2010) diarrhea and gastroenteritis ranks first on the pattern of 10 main diseases in hospitalized patients in the hospital, with  CFR  1.79%. This study aims to determine the factors related with  diarrhea in children aged 0-59 months in the  Simarmata Public Health Center Simanindo Samosir in 2013 . Design of this study was cross- sectional . The population in this study were all children aged 0-59 months in the Simarmata Public Health Center and samples taken at random is by simple random sampling , amounting to 126 people . Data obtained from interviews using questionnaires and observation . Data analysis includes univariate and bivariate analyzes . The results of this research got  the proportion of diarrhea in children aged 0-59 months in the Simarmata Public Health Center Simanindo Samosiy in 2013 was 36% . Results of the bivariate analysis showed  significant association between age (p = 0.018; RP = 1.998 ) , sex ( p = 0.018 ; RP = 1.761 ), personal hygiene (p = 0,037 ; RP = 1,625 )with  diarrhea in children aged 0-59 months and there is no significant relationship between mother educational ( p = 0.759 ; RP = 1.075 )  mother job (p= 0,296 ; RP = 0,623 ), waste management ( p = 0.491 ; RP = 1.188 ) , sewerage ( p = 0.064 ; RP = 1,615 ) , availability of latrines ( p = 0.389 ; RP = 1.277 ) , breastfeeding status exclusive ( p = 0.117 ; RP = 0.652 ) , nutritional status ( p = 0.172 ; RP = 1.472 ), measles immunization status (p = 0,970 ; RP = 0,533 ) with diarrhea in children aged 0-59 months . It is suggested that the Simarmata Public Health Center Simanindo Samosir to improve education and prevention about diarrhea such as to improve nutritional status, exclusive breastfeeding, and personal hygiene. Keywords : Diarrhea , Children Aged 0-59 Months , Environment